PEMBERDAYAAN MASYARAKAT MELALUI BANTUAN DANA DESA PADA DESA RITABEL KECAMATAN TANIMBAR UTARA KAPUBATEN KEPULAUAN TANIMBAR - Arter Maskikit; Normawati Normawati; ST N Ohoiwutun; Hengki Patimukay (Jurnal Ilmiah Global Education, 2023)
The ritable village community in Tanimbar Islands Regency is the outermost, outermost and deepest area so that the village government seeks to carry out an empowering response through managing village funds. The research method used is descriptive qualitative and conducting in-depth interviews. The research findings are (1). lack of professionalism of the village government in carrying out community empowerment programs. (2) Conflict of authority between village secretary and village head and lack of trust in leadership. (3). Weak community response in empowering programs provided by the village government